Assessing Nutrient Removal Kinetics in Flushed Manure Using Chlorella vulgaris Biomass Production - Pandey, Pramod; Shi, Jun (Frontiers in Bioengineering and Biotechnology, 2017)
The utilization of dairy wastewater for producing algal biomass is seen as a two-fold opportunity to treat wastewater and produce algae biomass, which can be potentially used for production of biofuels. In animal agriculture system, one of the major waste streams is dairy manure which contains high levels of nitrogen and phosphorous. Further, it is produced abundantly in California’s dairy industry, as well as many other parts of the world. We hypothesized that flushed manure, wastewater from a dairy farm, can be used as a potential feedstock after pretreatment to grow Chlorella vulgaris biomass, and to reduce nutrients of manure. In this study, we focused on investigating the use of flushed manure, produced in a dairy farm for growing Chlorella vulgaris biomass. A series of batch-mode experiments, fed with manure feedstock and synthetic medium, were conducted, and corresponding Chlorella vulgaris production was analyzed. Impacts of varying levels of sterilized manure feedstock (SMF) and synthetic culture medium (SCM) (20 – 100%) on biomass production, and consequential changes in total nitrogen and total phosphorous were determined. Chlorella vulgaris production data [1] were fitted into a model [2] for calculating kinetics of total nitrogen (TN) and total phosphorous (TP) removal. Results showed that the highest Chlorella vulgaris biomass production occurs, when SMF and SCM were mixed with ratio of 40%:60%. With this mixture, biomass on Day 9 was increased by 1740% compared to initial biomass, and on Day 30 it was increased by 2456.9%. The production was relatively low, when either only SCM or manure feedstock medium (MFM) [without pretreatment i.e., no sterilization] was used as a culture medium. On this ratio, TN and TP were reduced by 29.9% and 12.3% on Day 9, and these reductions on Day 30 were 76% and 26.9%, respectively.